Comparative study of energy efficient MAC protocol with channel aware packet Scheduling in MANET - Dheepak, T; Neduncheliyan, S (International Journal of Engineering and Technology, 2018)
Mobile Ad Hoc Network is the centralized communication system which is used for transferring information through a secured mode from one end to another end. However, there is an energy loss that has been noticed in MANET. In this work, an efficient energy based Link Failure State Neighbor Detection Effective Efficient Protocol (LFSNDEEP) is to enhance the energy efficiency of the mobile node, and optimal transmission ratio computes Data, Audio, and Video packets. The proposed research on LFSNDEEP protocol is compared to Effective Efficient Neighbor Detection Protocol (EENDP) and which assigns the channel utilization. In this technique, the hello packet exchanges transmit based height and wavelength of the transmitter with particular distance. The computation of channel utility factor is the best method at link failure without data loss. The vitality utilization mathematical model is illustrated to show the nodes of least consumption by the broad recreation of utilization. The results observed from the proposed scheme shows that the energy level is minimized regarding the packet that loss is improved efficiently. In further, there are two results which can be gained in comparing with EENDP; firstly, packet delivery ratio and throughput get increased. And secondly, the end to end delay is decreased.